Quorum sensing inhibition in Pseudomonas aeruginosa biofilms: new insights through network mining - Pérez-Pérez, Martín (2017)
Quorum sensing plays a pivotal role in Pseudomonas aeruginosas virulence. This paper reviews experimental results on antimicrobial strategies based on quorum sensing inhibition and discusses current targets in the regulatory network that determines P. aeruginosa biofilm formation and virulence. A bioinformatics framework combining literature mining with information from biomedical ontologies and curated databases was used to create a knowledge network of potential anti-quorum sensing agents for P. aeruginosa. A total of 110 scientific articles, corresponding to 1,004 annotations were so far included in the network and are analysed in this work. Information on the most studied agents, QS targets and methods is detailed. This knowledge network offers a unique view of existing strategies for quorum sensing inhibition and their main regulatory targets and may be used to readily access otherwise scattered information and to help generate new testable hypotheses. This knowledge network is publicly available at http://pcquorum.org/